COMPARATIVE ANALYSIS OF INCOME INEQUALITY PERCEPTIONS BY THE ELDERLY IN EUROPE AND RUSSIA: THE RELATIONSHIP BETWEEN ACTUAL AND PERCEIVED INCOME INEQUALITY - Elena A. Frolova; Elmira R. Kashapova; Veronika A. Malanina; Fabio Casati (Векторы благополучия: экономика и социум, 2021)
The article describes the attitude of the population to inequality by the elderly in European countries and Russia. The relevance of the study is caused by the to differences in the perception of inequality and its actual indicators, which affects the demand for state equalization policy tools, especially for older adults. The purpose of this study is to assess the relationship between actual and perceived inequality among the older generation in the EU and the Russian Federation. Methods. We have used the method of descriptive statistics on the samples of the 8th wave of the European social research (ESS-2016) for the age group of 60+ years in Russia and European countries. Data from the World Inequality Database (2017) and data from the OECD (2018) were used to assess actual inequality. Correlation analysis is used for assessment of the relationship between subjective and actual inequality indicators. Results. A comprehensive assessment of the perception of inequality among older people in the Russian Federation is close to the average values for EU countries. However, there are differences from the European average in the level of tolerance to inequality due to personal effort and opportunities, and in estimates of equality of opportunity. Correlations between actual and subjective indicators of inequality showed that there is an inverse correlation between estimates of living standards and the legitimacy of talent and effort, the Gini coefficient and the standard of living indicator (GDP per capital). Indicators of actual inequality showed a close direct relationship with the risks of poverty of older people. There is no statistically significant relationship between income differentiation and a comprehensive assessment of the perception of inequality.